Analysis of the Impact of Education on Poverty in Cameroon: An Application of the Nested Logit Model (Global Journal of Management and Business Research, 2020)
This paper re-examine the relationship between human capital and poverty. Using data from the Third National Household Survey in Cameroon (ECAM 3), and a nested logit model, this study shows that education alleviates poverty of people living close to the poverty line in Cameroon. Conversely, when the poor fall far below the poverty line the cost associated with education acquisition process tends to have a negative impact on their abilities to meet their basic needs for households in Cameroon. These results suggest that financially support the education of the poorest will lift them out of poverty.
Keywords: education; well-being; poverty; nested logit model